Comprehensive retention model for PFAS transport in subsurface systems. (1st January 2019) - Brusseau, Mark L.; Yan, Ni; Van Glubt, Sarah; Wang, Yake; Chen, Wei; Lyu, Ying; Dungan, Barry; Carroll, Kenneth C.; Holguin, F. Omar
Abstract: A comprehensive compartment model is presented for PFAS retention that incorporates all potential processes relevant for transport in source zones. Miscible-displacement experiments were conducted to investigate separately the impact of adsorption at the air-water and decane-water interfaces on PFAS retention and transport. Two porous media were used, a quartz sand and a soil, and perfluorooctanesulfonic acid (PFOS) was used as the model PFAS. The breakthrough curves for transport under water-unsaturated conditions were shifted noticeably rightward (delayed arrival) compared to the breakthrough curves for saturated conditions, indicating greater retardation due to adsorption at the air-water or decane-water interface. The retardation factor was 7 for PFOS transport in the sand for the air-water system, compared to 1.8 for saturated conditions. PFOS retardation factors for transport in the soil were 7.3 and 3.6 for unsaturated (air-water) vs saturated conditions. Air-water interfacial adsorption is a significant source of retention for PFOS in these two systems, contributing more than 80% of total retention for the sand and 32% for the soil. For the experiments conducted with decane residual emplaced within the sand, adsorption at the decane-water interface contributed more than 70% to total retention for PFOS transport. Methods to determine or estimate key distribution variables are presented for parameterization of the model. Predicted retardation factors were similar to the measured values, indicating that the conceptual model provided adequate representation of the relevant retention processes and that the parameter estimation methods produced reasonable values. The results of this work indicate that adsorption by fluid-fluid interfaces in variably saturated porous media can be a significant retention process for PFAS that should be considered when characterizing their transport and fate behavior in source zones. Graphical abstract: Highlights: A comprehensive retention model for PFAS is developed. Transport experiments are conducted for PFOS and PFOA. Retardation is greater for unsaturated conditions due to air-water interfacial adsorption. Retardation is greater in the presence of NAPL due to NAPL-water interfacial adsorption. The model provides good predictions of retardation.